Employee commitment and performance - Meyer, John; Stanley, D. (Edward Elgar Publishing, 2016)
Commitment in the organizational context has been the focus of thousands of journal articles. Although interest was stimulated initially by its implications for employee retention, questions about its effects on performance also arose, particularly ...